Impacts of Solid Waste Management on Environment and People of Kekubo-Kabale Municipality. - Ayebazibwe, Daphine (Kabale University, 2024)
This study examined the environmental and socio-economic factors influencing waste management practices in Kekubo, Kabale, Uganda. It explored how factors such as income, education, and age distribution impact the community's involvement in waste management, focusing on waste types like plastics, glass, medical waste, textiles, polythene, domestic waste, and paper. Data were collected through questionnaires distributed to various demographic groups, categorized by income and education levels. The findings indicate that socio-economic status and educational level play a significant role in shaping the community's environmental awareness and waste management practices. Higher-income and education levels were linked to more active participation in sustainable waste management activities. The study revealed that domestic waste was the largest waste category, emphasizing the need for effective household waste management strategies. Gender disparities were also noted, with females generally more involved in waste generation and awareness activities, pointing to the need for interventions to promote gender-balanced participation. The study concludes that successful waste management in Kekubo requires inclusive strategies that address socio-economic diversity, alongside educational programs and incentives to encourage greater community involvement. Additionally, the research highlights limitations, including the need for improved data collection methods and the challenge of turning awareness into actionable behavior change. The findings emphasize the importance of community-driven, collaborative approaches to achieving sustainable environmental management in the area.